Pengaruh Gaji Guru dan Motivasi Kerja Terhadap Kinerja Guru pada SDIT Al-Muddatsiriyah - Farid Wajdi; Didin Hikmah Perkasa (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to determine the effect of teacher salaries and work motivation on the performance of SDIT Al-Muddatsiriyah Jakarta teachers partially and simultaneously. Data is processed using SPSS v. 24. This study uses a quantitative approach through the results of interviews and questionnaires. Sampling taken from the entire population produced 50 respondents. The analysis used includes validity test, reliability test, classic assumption test, multiple linear regression test, test coefficient of determination, and hypothesis testing. The results of the study found that: 1.) partially teacher salaries had a significant effect on teacher performance with thitung (5,815)> t table (2012) 2.) partially work motivation had a significant effect on teacher performance with tcount (3,732)> t table (2012) 3 .) Simultaneously teacher salaries and work motivation have a significant effect on teacher performance with Sig. (0,000) <(0,05).